A novel player in the field: Merkel disc in touch, itch and pain. Issue 12 (20th May 2019) - Feng, Jing; Hu, Hongzhen
Abstract: The mechanosensitive Merkel cell‐neurite complex comprising two distinct cell types in both hairy and glabrous skin has been widely recognized as touch receptor for more than 100 years. In 2014, three elegant studies further demonstrated that the Merkel cell‐neurite complex mediates touch transduction via the mechanosensitive Piezo2 channel. However, whether it is involved in genesis of itch and pain sensations, has been unclear. Recently, we reported that Merkel cells modulate the development of mechanical itch under the conditions of dry skin and aging, whereas two other studies demonstrated that Piezo2 channel mediates mechanical pain. In this assay, we summarized the current knowledge of Merkel disk under both normal and pathological conditions, with a focus on its role in touch, itch, and pain.